2020
DOI: 10.1590/1983-1447.2020.20190281
|View full text |Cite
|
Sign up to set email alerts
|

SNOMED-CT as a standardized language system model for nursing: an integrative review

Abstract: Objective: To describe the use of the Systematized Nomenclature of Medicine - Clinical Terms (SNOMED-CT) as a model for interoperability of the nursing terminology in the national and international contexts. Methods: This is an integrative literature review according to Cooper, which searched for articles in Portuguese, English and Spanish, published between September 2011 and November 2018 in the BVS, PubMed, SCOPUS, CINAHL, EMBASE, and Web of Science databases, ending in a sample of 15 articles. Results: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…This study focuses on the links between individual care, community-based activities, and project development to assess the need for continued care. Most studies showed the framework and items of nursing assessment, interventions, and outcomes for individual patients [10][11][12][13][14]. By contrast, PHNs promote health equity and individual, family, and community health through direct care and policy development [15].…”
Section: Principal Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…This study focuses on the links between individual care, community-based activities, and project development to assess the need for continued care. Most studies showed the framework and items of nursing assessment, interventions, and outcomes for individual patients [10][11][12][13][14]. By contrast, PHNs promote health equity and individual, family, and community health through direct care and policy development [15].…”
Section: Principal Findingsmentioning
confidence: 99%
“…Clinical terminology or taxonomy and its framework help visualize the classification of patients and nursing practice and improve health equity in multidisciplinary settings [9][10][11][12][13][14]. Nursing practices are based on nursing diagnosis systems [11] and interventions [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Classifications, health taxonomies, and theories can be combined for factor‐relating theorization, providing a framework for organizing concepts, such as the domains and diagnostic classes of the NANDA‐International Taxonomy. For example, the terminological classification of SNOMED CT includes relationships to associate two concepts and logically defines the meaning of a concept in a way that a computer can process (Ceusters & Bona, 2016; Silva et al., 2020).…”
Section: Introductionmentioning
confidence: 99%